HASIL BELAJAR KETERAMPILAN MEMBACA BAHASA JERMAN DENGAN PENGGUNAAN MEDIA BIG BOOK PESERTA DIDIK KELAS X SMAN 1 SOOKO MOJOKERTO - MILADYAH FAUZAN, RIZKA (LATERNE, 2018)
This study examines the outcomes of learning the German language reading skills of students class X IPS-1 SMAN 1 Sooko Mojokerto. Learning of reading skills are not easy to learn if Students are not used to reading texts. Reading skills are important skills because it can affect proficiency in other language skills. Therefore, for learners interested, happy, and have a high motivation to read, used Big Book media that will facilitate learners in the learning process. The formulation of the problem in this research is